The Relationship Between The Health Centre Service Quality And Facilities With Inpatients Loyalty: The Health Centre Service Quality - Sri Mulyani; Muhammad Ikhsan Akbar (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background : The quality of services and facilities at the health centre which are still very limited have resulted in complaints that are often heard from health service users in the form of low loyalty to the health services provided which can lead to a decrease in the number of visits over time. The purpose of this study was to determine the relationship between quality of service and facilities at the health centre with inpatient loyalty Methods: The type of research used is quantitative research with a Cross Sectional Study design. The population in this study were all patients who had been hospitalized at the health centre, with a total sample of 95 patients selected using a simple random sampling technique. Results: The results of the bivariate analysis showed that the patient's perceived low loyalty was 17( 29.82 % )in patients with poor reliability assessment, 27 ( 47.37 %) in patients with poor responsiveness, 9 ( 33.33 %) in patients with poor attention and23 ( 40.35 %) in patients who felt that the health centre facilities were lacking. The results of statistical tests using the Chi-Square test obtained a significance value that was lower than the alpha value so that it could be concluded that the variables of reliability, responsiveness, attention, health center facilities had an effect on inpatient loyalty with the value of each p- value: 0.000; 0.020; 0.031; 0.049. Conclusion: This study proves that the reliability, responsiveness, attention and facilities of the health centre are related to inpatient loyalty. There needs to be a policy by the service provider, in this case, the manager of the Health centre staff in improving the quality of health centre services.